2011
DOI: 10.1002/etc.501
|View full text |Cite
|
Sign up to set email alerts
|

Uptake from water, biotransformation, and biliary excretion of pharmaceuticals by rainbow trout

Abstract: An urgent need exists to assess the exposure of fish to pharmaceuticals. The aim of the present study was to assess the uptake and metabolism of waterborne pharmaceuticals in rainbow trout (Oncorhynchus mykiss). A further objective was to determine the possibility of monitoring exposure to low levels of pharmaceuticals by bile assays. Rainbow trout were exposed for 10 d under flow-through conditions to mixtures of five pharmaceuticals (diclofenac, naproxen, ibuprofen, bisoprolol, and carbamazepine) at high and… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

7
68
0

Year Published

2012
2012
2022
2022

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 118 publications
(75 citation statements)
references
References 45 publications
7
68
0
Order By: Relevance
“…Several studies have reported effects on fish at these concentrations of diclofenac, ranging from cytological and histological effects [14][15][16][17] to effects on gene expression [15,18]. Reported bioconcentration factors (BCFs) for diclofenac in rainbow trout varies between studies [10,11,16,18,19]. However, the most recent studies are in relatively close agreement, showing a stable BCF from water to blood plasma of approximately 4 [18,19].…”
mentioning
confidence: 73%
See 1 more Smart Citation
“…Several studies have reported effects on fish at these concentrations of diclofenac, ranging from cytological and histological effects [14][15][16][17] to effects on gene expression [15,18]. Reported bioconcentration factors (BCFs) for diclofenac in rainbow trout varies between studies [10,11,16,18,19]. However, the most recent studies are in relatively close agreement, showing a stable BCF from water to blood plasma of approximately 4 [18,19].…”
mentioning
confidence: 73%
“…Reported bioconcentration factors (BCFs) for diclofenac in rainbow trout varies between studies [10,11,16,18,19]. However, the most recent studies are in relatively close agreement, showing a stable BCF from water to blood plasma of approximately 4 [18,19]. We have recently shown effects on the global hepatic gene expression at exposure concentrations of diclofenac down to 1.6 g/L, even though the corresponding plasma concentration of exposed fish was relatively low (approximately 6 ng/mL) in comparison with the human therapeutic plasma concentrations (HTPC) of >420 ng/mL [20,21].…”
mentioning
confidence: 99%
“…In addition to the dosing experiments of this marine species with CBZ, bile was harvested and profiled for drug metabolites after administration of IBU. The findings obtained for the marine fish were contrasted with those reported for rainbow trout inhabiting freshwater environments [15,21]. The work presented here was carried out as part of a broader study on the biological interactions of human drugs with hepatic enzymes in fish [22].…”
Section: Introductionmentioning
confidence: 83%
“…For example, the popular non-steroidal anti-inflammatory drugs, diclofenac, naproxen and ibuprofen, were all shown to accumulate in fish (Lahti et al 2011). The concentration of ibuprofen determined in the fish plasma and bile samples was 100 to 1000-fold higher than in corresponding water samples (Jeffries et al 2015).…”
Section: Fate Of Pharmaceuticals In the Freshwater Environmentmentioning
confidence: 97%